Successful Modified Therapy in a Patient with Probable Infection-Associated Hemophagocytic Lymphohistiocytosis - Carl L. Kay; Matthew J. Rendo; Paul Gonzales; Sead G. Beganovic; Magdalena Czader (Case Reports in Oncological Medicine)
Hemophagocytic lymphohistiocytosis (HLH) is a rare, hyperinflammatory syndrome characterized by clinical signs and symptoms of extreme inflammation. In adults, HLH is typically a complication of infections, autoimmune diseases, and malignancies. While the disease is often fatal, classic management of HLH revolves around early diagnosis and initiation of protocolized therapy. We present a case of a previously healthy 56-year-old female who developed distributive shock requiring intubation, vasopressors, and continuous venovenous hemofiltration. In the setting of multiple infectious syndromes, severe cytopenias, and rising direct hyperbilirubinemia, her diagnosis of HLH was confirmed. Therapy was initiated with dexamethasone and two doses of reduced-intensity etoposide based on the patient’s clinical course. Over the next few weeks, she continued to improve on dexamethasone monotherapy and has maintained remission up to the present with complete resolution of her cytopenias and return of baseline renal function. Our case highlights the variability in the management of probable infection-associated HLH (IHLH) with a good patient outcome. We demonstrate the potential to treat IHLH with partial protocols and minimal chemotherapeutics.